PENGARUH STRES KERJA, LINGKUNGAN KERJA FISIK, KESELAMATAN DAN KESEHATAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA CV. BALI IMAGE COLLECTION DI BATUBULAN, GIANYAR - A.A.Made Alit Putra; Nengah Landra; Ni Made Dwi Puspitawati (VALUES, 2022)
The success and success of a company is largely determined by how the company manages its resources. The role of human resources in the company is a very vital factor to carry out functions and achieve company goals. Therefore, companies need to understand and treat employees appropriately. Employee job satisfaction is a phenomenon that is often encountered in a company and employee job satisfaction must also be a concern of the company. Low employee job satisfaction will affect the level of absenteeism, labor turnover, morale, complaints and other vital personnel problems. This study aims to analyze the effect of work stress, physical work environment, occupational safety and health on employee job satisfaction at CV. Bali Image Collection in Batubulan, Gianyar . The number of samples in this study were 46 employees of CV. Bali Image Collection in Batubulan, Gianyar. The sampling technique used in this study is the census/saturated method (saturated sample). The data analysis technique used is multiple linear regression analysis. The results showed that job stress had a negative and significant effect on employee job satisfaction at CV. Bali Image Collection in Batubulan, Gianyar. While the physical work environment, occupational safety and health have a significant positive effect on employee job satisfaction at CV. Bali Image Collection in Batubulan, Gianyar. These results indicate that employee job satisfaction in CV. Bali Image Collection In Batubulan, Gianyar must be maintained and cared for, especially related to work stress, physical work environment, and employee safety and health.